Management of Behcet's disease - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Purpose of review Current treatment modalities in Behcet's disease will be summarized in light of new studies published within the last 2 years. Recent findings There is an increasing interest in the treatment of refractory mucocutaneous symptoms of Behcet's disease, and results were quite promising with apremilast, anakinra, and ustekinumab. Data from large case series confirmed both the efficacy and safety of tumor necrosis factor-alpha inhibitors for the treatment of refractory major organ manifestations such as ocular, neurologic, vascular, and gastrointestinal involvement. In refractory ocular disease, long-term results also confirmed the efficacy and safety of interferon-alpha. Interleukin-1 inhibitors and tocilizumab seem to be alternative options in patients with refractory ocular involvement. Summary Prospective and controlled studies for the management of major organ involvement in Behcet's disease are still limited. Data from primarily retrospective studies confirmed better outcomes of major organ involvement with tumor necrosis factor-alpha inhibitors and interferon-alpha . There were also acceptable results with interleukin-1 inhibitors for the management of refractory ocular disease, and with apremilast, anakinra, and ustekinumab for refractory mucocutaneous involvement.
Keywords: Behcet's disease; interferon-alpha; interleukin-1 inhibitors; tumor necrosis factor-alpha inhibitors; tocilizumab; ANTI-TNF-ALPHA; DOUBLE-BLIND; INTERFERON ALPHA-2A; REMISSION INDUCTION; CLINICAL-OUTCOMES; CASE SERIES; ADALIMUMAB; THERAPY; MULTICENTER; EFFICACY